2015
DOI: 10.1002/adma.201502339
|View full text |Cite
|
Sign up to set email alerts
|

Optical Anisotropy and Strong H‐Aggregation of Poly(3‐Alkylthiophene) in a Surface Monolayer

Abstract: Slab optical waveguide absorption spectra reveal that surface segregated monolayers of a vertically oriented poly(3-buthylthiophene) derivative have large optical anisotropy, and that confinement of the polymer chains in the isolated monolayer causes strong H-aggregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 51 publications
3
16
1
Order By: Relevance
“…This value is only a little higher than the value calculated from the molecular formula (0.026 based on the assumption of the average n of 14). This is in contrast to P3BT-F 17 in which F/C atomic ratio at the film surface is much higher than those calculated from the molecular formula (0.27 vs. 0.11), suggesting the surface is preferentially covered with the fluoroalkyl chains [10]. Therefore, this result suggests that P3BT-Si segregate on the surface of PS film but P3BT-Si at the surface does not have strong preferential surface display of the trisiloxane moiety.…”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…This value is only a little higher than the value calculated from the molecular formula (0.026 based on the assumption of the average n of 14). This is in contrast to P3BT-F 17 in which F/C atomic ratio at the film surface is much higher than those calculated from the molecular formula (0.27 vs. 0.11), suggesting the surface is preferentially covered with the fluoroalkyl chains [10]. Therefore, this result suggests that P3BT-Si segregate on the surface of PS film but P3BT-Si at the surface does not have strong preferential surface display of the trisiloxane moiety.…”
Section: Resultscontrasting
confidence: 63%
“…Note that complete conversion of the chain ends from -Br to -H would be possible by the reduction reaction with NaBH 4 [14]. However, we did not observe significant influence of -Br/-H ratio on the surface segregation behavior and the molecular orientation in the case of P3BT-F 17 [9,10]. Therefore, we speculate the effect of the end group is also small for P3BT-Si.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Face‐on orientations of P3HT in thin films can be induced by the proper choice of solvent, mechanical strain, and surface rubbing of the films . There are still limited examples of the end‐on orientation of polymer chains in films . The molecular orientation can strongly affect the photophysical processes in PHJs in many ways, as discussed in Sections and .…”
Section: Preparation and Characterization Of Planar Heterojunctionsmentioning
confidence: 99%
“…SSMs were originally developed to form self‐organized buffer layers at the electrode interfaces in OPVs . Later, it was shown that proper design of SSM molecules can control the molecular orientation, structural order, and functionalities at the surface of the films . Furthermore, the electronic structures of the PHJ at the interface can be tuned through the molecular dipoles or the energy structures of the monolayers .…”
Section: Preparation and Characterization Of Planar Heterojunctionsmentioning
confidence: 99%